Village land governance: Compliance with village land-use planning in selected communities in Tanzania - Pius John Nyamhanga; Emmanuel Timothy Malisa; Samwel J. Kabote (Heliyon)
Village land and village land governance are critical for the livelihoods of rural communities in Tanzania. However, compliance with the institutional frameworks, imperative for the village land governance, is poorly understood. This study employed an exploratory sequential research design to address this knowledge lacuna in Kilosa and Mvomero districts in Tanzania. Qualitative data were collected through Focus Group Discussions and key informant interviews, while quantitative data were collected from 120 randomly selected respondents through a survey method. We employed thematic analysis for qualitative data and a binary logistic regression model for quantitative data. Qualitative results were in line with quantitative results. Half of the respondents acquired land by a temporary lease. Although this is prescribed in the land laws, the results did not confirm compliance because two-thirds of the respondents worked on unplanned pieces of land, particularly in Kilosa District. Reducing the likelihood of working on unplanned land was significantly influenced by land law enforcement, knowledge of the outcomes of non-compliance with the land laws, and the number of plots owned by districts at a 5 % significance level. We conclude limited compliance with working on a planned land in the study area. This provides implications for enhancing knowledge of village land governance among the actors and improving the enforcement capacity of village land-use planning. Alternatively, the results articulate a need to devise mechanisms, including capacity building of local governance structures, technically and regarding resources, to implement and enforce land-use planning.